Targeting evolution to inhibit antibiotic resistance. (8th June 2020) - Merrikh, Houra; Kohli, Rahul M.
Abstract : Drug‐resistant bacterial infections have led to a global health crisis. Although much effort is placed on the development of new antibiotics or variants that are less subject to existing resistance mechanisms, history shows that this strategy by itself is unlikely to solve the problem of drug resistance. Here, we discuss inhibiting evolution as a strategy that, in combination with antibiotics, may resolve the problem. Although mutagenesis is the main driver of drug resistance development, attacking the drivers of genetic diversification in pathogens has not been well explored. Bacteria possess active mechanisms that increase the rate of mutagenesis, especially at times of stress, such as during replication within eukaryotic host cells, or exposure to antibiotics. We highlight how the existence of these promutagenic proteins (evolvability factors) presents an opportunity that can be capitalized upon for the effective inhibition of drug resistance development. To help move this idea from concept to execution, we first describe a set of criteria that an 'optimal' evolvability factor would likely have to meet to be a viable therapeutic target. We then discuss the intricacies of some of the known mutagenic mechanisms and evaluate their potential as drug targets to inhibit evolution. In principle, and as suggested by recent studies, we argue that the inhibition of these and other evolvability factors should reduce resistance development. Finally, we discuss the challenges of transitioning anti‐evolution drugs from the laboratory to the clinic. Abstract : Bacteria can activate a variety of mechanisms to accelerate their access to genotypic variants, some of which can convert antibiotic‐susceptible bacteria into antibiotic‐resistant ones. These active mutagenesis mechanisms are ripe candidates for the development of anti‐evolutionary therapies, offering a novel and needed and novel approach to combating the challenge of antibiotic resistance.